Open study

is now brainly

With Brainly you can:

  • Get homework help from millions of students and moderators
  • Learn how to solve problems with step-by-step explanations
  • Share your knowledge and earn points by helping other students
  • Learn anywhere, anytime with the Brainly app!

A community for students.

Prove that if \[x+\frac{1}{x}=2 \cos \alpha,\] then \[x^n+\frac{1}{x^n}= 2\cos n \alpha.\]. [This problem is based on DeMoivre's theorem]

See more answers at
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly


Get your free account and access expert answers to this and thousands of other questions

I have done like this: - Let \[x= e^{i \theta}\]&\[\frac{1}{x}=e^{-i \theta}\]This approach is also given in my book. But now how to do further ? This is my actual problem.
\[x+\frac{1}{x}=2\cos \alpha\]only when x=1 and \(\alpha\)=0 This relation is not satisfied by any other values.

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

So, the second part goes accordingly!
\[r\left(e^{i\theta} + e^{- i \theta}\right) = 2\cos \alpha\]
Contd. \(x^n\)=1 and n\(\alpha\)=0 for any value of zero Remember we already have x=1 and \(\alpha\)=0
\[x^n = e^{ni\theta}\]
I gt that but isn't there logical way @ujjwal ?
*n In my last reply zero=n..
\[x^n + \frac1{x^n} = e^{ni\theta}+e^{n-i\theta} = \cos n \theta + i\sin n\theta +\cos n \theta - i\sin n\theta = 2\cos n \theta \]
I know that is informal and there must be a very formal way to derive that relation.. And @Ishaan94 is giving it to you.
oh ok i see :) thanx to all for the help :)

Not the answer you are looking for?

Search for more explanations.

Ask your own question